Effect of Paddy Straw plus Non-Forage Fibre Sources Based Complete Rations with Different Levels of Neutral Detergent Fibre on Rumen Fermentation Parameters in Lactating Cows - Chacko, K. Biju; Mohan, K.M. Syam; Ally, K.; Shyama, K.; Anil, K. S.; Sathian, C. T. (Indian Journal of Animal Nutrition, 2017)
Eighteen dairy cows yielding approximately 10 kg of milk/d were divided into 3 groups of six each and allotted to the three experimental rations containing 25, 30 and 35% NDF in groups T1, T2 and T3, respectively to study rumen fermentation parameters and occurrence of sub-acute ruminal acidosis (SARA). Paddy straw was the sole source of roughage NDF with the rest of NDF being met from non-forage sources. The pH of rumen liquor was similar among the treatments. The TVFA content was highest (P<0.05) in group T3 followed by T2 and T1 with the values being 73.71, 80.51 and 83.68 meq./L in groups T1, T2 and T3, respectively. The rumen ammonia production was lower (P<0.05) in group T3 than T1 and T2. There was no incidence of SARA in any of the cows in the three dietary treatments. These results suggested that complete rations containing paddy straw as the sole source of roughage with the rest of NDF being met from non-forage sources having a total NDF of 25 to 35% NDF can be recommended for use during early and mid lactation.